Quantitative Runge Approximation and Inverse Problems. (19th January 2018) - Rüland, Angkana; Salo, Mikko
Abstract: In this short note, we provide a quantitative version of the classical Runge approximation property for second-order elliptic operators. This relies on quantitative unique continuation results and duality arguments. We show that these estimates are essentially optimal. As a model application, we provide a new proof of the result from [8 ], [2 ] on stability for the Calderón problem with local data.